Local Government as Organiser of Cultural Institutions. Remote Governance with the Example of Public Libraries in the Pomeranian Voivodeship: Remote governance with the example of public libraries - Zbieranek, Piotr (Studia z Polityki Publicznej, 2024)
The article shows how the local government manages its network of local libraries. External circumstances are forcing the local government to seek savings by closing some libraries and putting pressure on the remaining establishments for organisational change. This transformation is to take place in four areas - widening accessibility, functionality, collaboration, audiences. The implementation of the changes is to be enabled by resources acquired from external sources. The method of transformation is to be determined by a normative model inspired by external - usually national - entities of different nature. The local government tries to disseminate this normative pattern to library managers in a variety of ways. The range of interactions to which library facilities are subject can be seen as ’governance at a distance’ (Miller and Rose 1990, 1992). This article is an interpretation of the empirical material collected as part of the research on the library network in the Pomeranian Voivodeship carried out in 2022 and 2023, which included individual in-depth interviews and questionnaire surveys with representatives of local government units.